The handbook of social and political conflict - Samoilenko, Sergei A., 1976-; Simmons, Solon (John Wiley & Sons, Inc., 2025)
"The 2016 and 2020 U.S. presidential elections will be remembered for years as a fierce clash between polarized views, ideologies, and values embedded in an ongoing political and social conflict. The extreme partisanship of contemporary American politics has deepened an ideological cleavage between liberals and conservatives on a number of topics including gun control, taxes, and abortion, and climate change. The academic community has been working on the notions of political and social conflict for many years. However, this research was never translated into a symbiotic body of knowledge helping scholars and practitioners to understand conflict as an adjustable social construct transformed by the realities of a mediatized society. The Handbook of Social and Political Conflict proposes to fill the gap by making state-of-the-art research available to students, scholars, and practitioners. Including coverage of topical issues such as social justice movements, culture' and character assassination, misinformation, and the politicization of science among many others, this Handbook provides a thorough examination of the myriad ways in which conflict is manifested in our mediatized society. Interdisciplinary in approach with coverage of global political conflict and social issues, The Handbook of Social and Political Conflict provides a comprehensive overview of intercultural, international, intergenerational and ideological conflict and its resolution, while providing research to help the reader critically evaluate the effectiveness of methods of response to conflict and develop critical thinking regarding conflict resolution. Suitable for students and scholars of both Communication & Media Studies and Political Sciences, and applicable to many other disciplines touching on social justice, social media, and environmental issues"-- Provided by publisher.
Keywords: Social conflict.; Political sociology.; Polarization (Social sciences); elektronické knihy; electronic books